Introduction to RF simulation and its application - Kundert, K. (Proceedings of the 1998 Bipolar/BiCMOS Circuits and Technology Meeting (Cat. No.98CH36198), 1998)
RF circuits exhibit several distinguishing characteristics that make them difficult to simulate using traditional SPICE transient analysis. The various extensions to the harmonic balance and shooting method simulation algorithms are able to exploit these characteristics to provide rapid and accurate simulation for these circuits. This paper is an overview of RF simulation beginning with the characteristics of RF circuits that distinguish them from traditional analog circuits. Harmonic balance and shooting methods are described along with several important extensions. The emphasis is on presenting the algorithms at a conceptual level to provide a basic understanding of the operation and capabilities of the algorithms. Finally, it is shown how these techniques are applied to make common RF measurements.